2019
DOI: 10.3390/min9090555
|View full text |Cite
|
Sign up to set email alerts
|

Methylene Blue Adsorption Study on Microcline Particles in the Function of Particle Size Range and Temperature

Abstract: In this paper, the adsorption process of methylene blue has been investigated on microcline particles as a function of particle size and temperature. The characterization of microcline in the particle size ranges of 1−71 μm and 71−315 μm gained by sieving was proved using X-ray diffraction (XRD) and scanning electron microscopy combined with energy-dispersive detector (SEM-EDS) in powder form, over laser diffraction measurements in aqueous suspension. The optimum dosage of adsorbent was 13.5 g/L in dye adsorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 40 publications
3
5
0
Order By: Relevance
“…The diffraction peaks of KMC are in good agreement with the reference library ICDD 19-926. Meanwhile, the XRD diffractogram of the microcline used for the adsorption of methylene blue showed similar identical diffraction peaks with our report 66 . On the other hand, the X-ray diffraction spectra obtained for KMCM showed no significant change with respect to the 2Theta values when compared to KMC.…”
Section: Resultssupporting
confidence: 87%
“…The diffraction peaks of KMC are in good agreement with the reference library ICDD 19-926. Meanwhile, the XRD diffractogram of the microcline used for the adsorption of methylene blue showed similar identical diffraction peaks with our report 66 . On the other hand, the X-ray diffraction spectra obtained for KMCM showed no significant change with respect to the 2Theta values when compared to KMC.…”
Section: Resultssupporting
confidence: 87%
“…Since the adsorbent determines the adsorbent capacity for a given initial concentration, the dosage of the adsorbent is an important parameter [ 187 ]. According to Kroeker’s rule, the specific adsorbed volume, for a constant initial concentration, decreases with increasing adsorbent mass [ 188 ]. Thus, increasing the adsorbent dose is positively correlated with the efficiency and performance of dye removal.…”
Section: Factors Affecting Adsorption Processmentioning
confidence: 99%
“…For the Furthermore, the diffusion path length of the cations through the adsorbent cations is essentially shortened, which also simplifies the sorption [38]. Pernyeszi et al [39] also reported that smaller adsorbent particle sizes have better sorption than larger particles due to a synergy between increased specific surface area and active sites.…”
Section: Influence Of Zeolite Particle Size On Removal Efficiency (E%)mentioning
confidence: 99%